Sol-gel coating formulations and methods for mitigating galvanic corrosion

A chromium-free sol-gel coating forms a dense electrical insulation layer to mitigate galvanic corrosion by limiting current exchange, achieving over 98% reduction in corrosion of aluminum structures.

JP2025501059APending Publication Date: 2025-01-17LUNA LABS USA LLC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024531551
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-20
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing corrosion mitigation methods for galvanic corrosion in metal structures, particularly between dissimilar materials, are inadequate in providing durable physical and electrical barriers, leading to significant corrosion of anodic materials.

Method used

A chromium-free, water/alcohol-based sol-gel coating with a highly cross-linked structure is applied to either the cathode or anode, forming a dense electrical insulation layer and physical barrier to reduce galvanic corrosion by limiting current exchange.

Benefits of technology

The sol-gel coating effectively reduces galvanic corrosion by over 98% in aluminum structures, providing superior protection against moisture and corrosive ions, and maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501059000007
    Figure 2025501059000007
  • Figure 2025501059000008
    Figure 2025501059000008
  • Figure 2025501059000009
    Figure 2025501059000009
Patent Text Reader

Abstract

Provided is a durable, pigmented, transparent inorganic-organic hybrid sol-gel coating material that mitigates galvanic corrosion of metal substrates. The coating material is generally an acid-catalyzed condensation reaction product of an organic polymeric silane (e.g., a polyol functionalized with a silane such as isocyanatopropyltrimethoxysilane or isocyanatopropyltriethoxysilane via a urethane bond or a polyamine functionalized with a silane via a urea bond), an inorganic metal alkoxide (e.g., a silicon alkoxide such as tetraethoxysilane or tetramethoxysilane), and a metal oxide nanoparticle such as silica (SiCte), which may contain other additives such as colorants and / or corrosion inhibitors.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 292,563 (Atty. Dkt. 8760-0009), filed December 22, 2021, the entire contents of which are expressly incorporated herein by reference.

[0002] Government Rights The disclosed aspects were made with support from the Office of Naval Research, Contract Nos. N00014-14-P-1231 and N68335-16-C-0121.

[0003] Technical Field Sol-gel coatings, optionally containing corrosion inhibitors, that mitigate galvanic corrosion on metal substrates by providing superior physical and electrical barriers, as well as enhanced passivation in corrosive environments, are disclosed. When applied to either the cathode (e.g., steel fasteners, rivets, bushings, etc.) or the anode (e.g., aluminum aircraft skins, automobile bodies, etc.), the coating acts to reduce the cathodic current density in the galvanic couple. This reduction in current leads to reduced corrosion of the anode. [Background technology]

[0004] Load-bearing structures utilize fasteners for mechanical attachment and gripping applications. Examples range from aircraft, bridges, buildings, automobiles, and numerous other structures around the world. The majority of applications require corrosion mitigation solutions to be implemented throughout the structure to increase survivability and service life. One prime example is aircraft, which require advanced corrosion solutions to maintain structural integrity and availability. In particular, cathodic fasteners located adjacent to anodic aluminum alloys can experience significant galvanic corrosion of the aluminum. Cathodic fastener materials include, but are not limited to, other metals, magnesium alloys, or carbon fiber reinforced polymer (CFRP) composites joined with aluminum structures composed of extreme corrosion resistant steels (CRES), titanium, copper-beryllium and nickel-based alloys, or alloys 7075-T6, 2024-T3, 7050-T7451. Some fastener locations may be particularly susceptible to corrosion because seawater and other chloride-containing electrolytes collect there, creating a severe occluded environment and aggressive attack. One aspect of the coating embodiments disclosed herein is to provide a novel form of galvanic corrosion protection mechanism to limit attack on aluminum structures and many other non-aircraft structures susceptible to galvanic attack.

[0005] To protect against corrosion in aircraft, aluminum alloys are routinely chromate conversion coated, primed with chromated epoxies, and topcoated with polyurethane. Similarly, fasteners may be coated with sacrificial metals (Cd, Zn-Ni, IVD, Al), pretreated with conversion coatings, and wet installed with sealants or primers. However, metal coatings can wear off during repeated handling and installation of fasteners, and defects in the primer / paint system during service are inevitable. Conventional anti-corrosion adhesive sol-gels are also disclosed in U.S. Pat. No. 10,508,205, the entire contents of which are expressly incorporated herein by reference.

[0006] Other potential galvanic corrosion applications are embodied by the present invention. Examples are numerous and can include applications where cathodic materials are fastened or joined to anodic metallic materials. Other possible examples include, but are not limited to, magnesium alloys (anodes) in contact with or containing cathodic fasteners (e.g. stainless steel, low alloy steels, nickel and titanium alloys, etc.); alloy steels with cathodic components attached (e.g. stainless steel fasteners, nickel and titanium alloys, etc.); and stainless steel alloys joined with cathodic materials such as nickel or titanium alloys. Applications are not limited to all-metal applications, as there are numerous examples where carbon or graphite, which is highly cathodic, may be placed in contact with metallic materials. In this situation, the carbon or graphite will drive the corrosion of the metallic material if an electrolyte is present. The present invention can find application as a protective coating when applied between such joined pairs, which are numerous and will be understood by those skilled in the art.

[0007] Galvanic corrosion between two dissimilar materials is controlled by the available cathodic current, which activates the anodic surface, leading to the breakdown of the passive film, the initiation of localized corrosion, and a drop in the local potential. To suppress this phenomenon, an easy-to-apply coating technology is needed that effectively reduces the cathodic driving force (i.e., current) of galvanic corrosion at the dissimilar material interface. Summary of the Invention

[0008] The embodiments disclosed herein provide a solution to this problem: a durable sol-gel coating designed to reduce galvanic corrosion by i) providing excellent physical barrier protection against moisture and corrosive ions, and ii) providing a durable, dense, electrically insulating layer between joined parts. The sol-gel coating ideally provides a highly crosslinked film that is chromium-free, free of the hazards associated with water / alcohol-based chemicals, and has excellent corrosion resistance, flexibility, and toughness. The coating system of the embodiments disclosed herein further allows for drop-in manufacturing of applications to galvanic materials and structural components by common coating application methods.

[0009] Coatings can be applied to components involved in an electrochemical galvanic couple to limit the galvanic corrosion effects of the anodic material. One prominent example is the application to fasteners and bushings used in aluminum aircraft structures. In this case, the coating is applied to the target fastener or bushing component (the cathode) and cured. The coated component is then installed in the aluminum aircraft structure by conventional methods. The coating limits the galvanic effects of the anode by limiting the current exchange between the bonding interfaces. The reverse is also true in that the coating may be applied to the anode (e.g., aluminum structure) and cured prior to bonding of the cathodic material. This concept can be extended to many other metal components, not just aircraft structures.

[0010] A preferred embodiment of the coating formulation for preventing galvanic corrosion comprises a galvanic corrosion preventing amount of an acid-catalyzed condensation reactant consisting of (i) an organic polymeric silane; and (ii) an inorganic metal alkoxide. The organic polymeric silane and the inorganic metal alkoxide may be present in a weight ratio of organic polymeric silane to inorganic metal alkoxide of about 1:9 to about 9:1, for example about 3:1.

[0011] The organic polymeric silane may be a silane-functionalized polyol or polyamine. For example, one particular embodiment includes a functionalized polycaprolactone polyol having 2 to 4 hydroxyl groups reacted with an isocyanate-terminated silane. The molecular weight of the functionalized polycaprolactone polyol may be 50 to 10,000 g / mol.

[0012] The organic polymeric silane may also be a polyurea silane, for example a reaction product of an amine having at least two primary or secondary amine groups with an isocyanate-terminated silane, for example a polyurea silane that is the reaction product of diethylenetriamine with an isocyanate-terminated silane.

[0013] The metal alkoxide component has at least one group of the formula Si(R 1 ) x (R 2 ) 4-x [In the formula, R 1 is C 1 ~C 8 Alkyl group, epoxide group, vinyl group, acrylic group, R 2 wherein x is a hydrolyzable alkoxy group or a halogen, and x is 0, 1, 2, or 3.

[0014] Certain embodiments of the coating formulations described herein optionally include 1 to 50 weight percent metal oxide particles having a diameter of 1 nm to 100 nm, based on the total weight of the coating formulation. Preferred metal oxide particles are represented by the formula M x O y where M is selected from the group consisting of Si, Ti, Zr, B, Al, Ge, V, Pb, Sn and Zn, and y is an integer. Substantially spherical nanoparticles of alumina, titania, silica and zirconia having an average diameter of 1-10 nm are especially preferred.

[0015] The coating formulation may further include colorants (e.g., organic color pigments or organic dyes) and / or corrosion inhibitors (e.g., compounds having one or more thiols, modified and unmodified hydrotalcite compounds, zinc phosphate, zinc oxide, cerium phosphate, cerium nitrate, cerium oxide, cerium aluminum oxide; strontium aluminum polyphosphate, and zinc aluminum polyphosphate).

[0016] These and other aspects of the present invention will become more apparent after careful consideration of the following detailed description of preferred exemplary embodiments of the invention.

[0017] With reference to the accompanying drawings, [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a photograph showing a representative coated glass coupon having the cured coating formulation of Table 1. [Diagram 2] FIG. 2 is a photograph showing a representative coated glass coupon having the cured coating formulation of Table 2. [Figure 3A-3B] 3A and 3B are photographs showing a 316 stainless steel flat panel (FIG. 3A) and a titanium alloy fastener (FIG. 3B), respectively, coated with the cured coating formulation of Table 2. [Figure 4] FIG. 4 is a graph of the electrochemical polarization sweep for uncoated 316 stainless steel compared to 316 stainless steel coated with the cured formulations of Table 2, with tests conducted at room temperature in pH 7, 3.5% NaCl starting from the open circuit potential to a maximum current density of 10 mA / cm2 at a sweep rate of 0.2 mV / s. [Figure 5A-5D]5A-5D are graphs of electrochemical impedance spectroscopy results for uncoated 316 stainless steel compared to 316 stainless steel coated with the cure formulations of Table 2 after immersion in 3.5% NaCl for 3.5 hours, with AC amplitude of 10 mV rms, 10 points per decade, and frequencies from 10 kHz to 10 mHz. [Figure 6A-6C] 6A-6C are photographs showing the appearance of three coatings prepared with different corrosion inhibitors applied to a glass substrate according to Example 3, FIG. 6A containing 7% Intelli-ion® AX1, FIG. 6B containing 10% Novinox® PAS, and FIG. 6C containing 12% cerium nitrate hexahydrate. [Figure 7A-7B] 7A-7B are photographs showing the results of various uncoated and coated 316 stainless steel fasteners bonded to aluminum alloy 7075-T6 panels before and after exposure to ASTM B117 salt spray for 14 days. [Figure 8] FIG. 8 is a photograph showing the results of various coatings after being applied to an aluminum alloy 7075-T6 panel, scribed down to the bare substrate, and subjected to ASTM B117 salt spray for 14 days. [Figure 9A-9B] 9A and 9B are photographs of uncoated Ti-6Al-4V and 316 stainless steel fasteners installed on a painted 7075-T6 aluminum alloy panel (FIG. 9A) compared to the sol-gel coated fasteners (FIG. 9B) before and after 500 hours of ASTM B117 salt spray and coating removal, clearly showing the significant reduction in galvanic corrosion of the 7075-T6 aluminum panel when the hardware was coated with the sol-gel coating formulation. [Figure 10A-10B]10A and 10B are photographs of 316SS hardware treated with a commercial corrosion protection product (AC-131) (FIG. 10A) and 316SS hardware coated with a sol-gel formulation according to an embodiment of the present disclosure (FIG. 10B) after 3000 hours of ASTM B117 salt spray and coating removal, clearly showing the significant reduction in galvanic corrosion of 7075-T6 aluminum panels when the hardware is coated with the sol-gel coating formulation. [Figure 11] FIG. 11 is a graph showing the calculated anodic charge passed relative to the measured damaged downhole of the fastener shown in FIGS. 10A and 10B after 500 hours of ASTM B117 salt spray, demonstrating a greater than 98% reduction in corrosion damage using the sol-gel coating formulations described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Detailed Description Sol-gel derived coatings are of interest in passivating metals, including aluminum and steel, due to their inherent properties, including density, low porosity, ease of formulation, and lack of toxicity, and their ability to form a dense barrier against the penetration of water and corrosion initiators. There has been significant research in the art into the development of these coatings as environmentally friendly alternatives to highly toxic chromate conversion coatings. The embodiments disclosed herein build on this research to produce highly durable versions of such environmentally friendly coating materials.

[0020] Inorganic-organic sol-gel coating materials formed from metal alkoxides are well known. In general, sol-gel materials are formed by a mixture of starting components that form a viscous liquid phase as a result of hydrolysis and condensation. Thus, the sol-gel process produces organically modified inorganic materials that are harder than traditional organic polymers. In a particularly preferred embodiment, a highly durable coating material is provided that includes inorganic particulates uniformly dispersed throughout a polymer matrix that hardens in an ambient environment. When the components of the system are mixed with a suitable catalyst, the coating formulation can be applied to a substrate surface and cured thereon to form a highly durable coating.

[0021] As previously described, the durable, transparent inorganic-organic hybrid coatings for metal substrates according to the embodiments described herein are generally acid-catalyzed condensation reaction products composed of organic polymeric silanes, inorganic metal alkoxides, and optionally colorants, metal oxide particles, and / or corrosion inhibitors. As will be appreciated by those skilled in the art, other materials such as different catalysts, surfactants, leveling agents, solvents, etc. may be used for this purpose.

[0022] A. Organic polymer silane Coating materials according to embodiments described herein necessarily comprise one or more organosilanes having the general structure RxSi(OR')y, where R is an organic ligand selected from alkyl, epoxide, amine, ether, acrylic, vinyl or polymers / oligomers thereof; x is the number of organic substituents (0-4); Si is silicon; R' is a hydrolyzable / condensable group selected from hydroxyl, chloro, bromo, methoxy, ethoxy, isopropoxy, n-propoxy, isobutoxy, and n-butoxy groups; y is the number of hydrolyzable substituents (0-4). The organosilanes are preferably polymeric silanes, where the R groups are oligomers or polymers including, but not limited to, epoxy, polyurethane, polyurea, silicone, polyether, polyester, polyamide, acrylate, etc., and have one or more of the above hydrolyzable silane groups.

[0023] The organic polymeric silane more preferably comprises either a polyol (including but not limited to diols, triols, tetraols, pentols, etc.) or polyamine silane-functionalized with a metal alkoxide (e.g., isocyanate-terminated silane) via a urethane bond, or a polyamine silane-functionalized with a metal alkoxide via a urea bond. The reaction between the polyol and the isocyanate-terminated silane may use an organometallic catalyst such as tin, zinc, bismuth, etc. Other polyols derived from polyesters, polyethers, polycarbonates, etc. may also be used.

[0024] In a preferred embodiment, the polyol or polyamine is silane functionalized with isocyanatopropyltrimethoxysilane or isocyanatopropyltriethoxysilane via a urethane or urea linkage, respectively.

[0025] Polyurethane silanes can be prepared from a wide range of molecular, oligomeric or polymeric polyether or polyester-based polyols having at least two hydroxyls, preferably three or four hydroxyls. Polyols having molecular weights of 50 to 10,000 g / mol, preferably 1000 to 2000 g / mol, may be used. For example, CAPA™ brand polyester polyols available from Perstorp Corporation or ARCOL® brand polyether-based polyols available from Bayer Material Science may be used.

[0026] Representative polyester polyols and polyether polyols including polycaprolactone diols or triols, polyethylene oxide diols or triols, polypropylene diols and triols, and having the weight average molecular weights listed above, can be satisfactorily used. Preferably, a polycaprolactone triol having the following structure: [ka] [In the formula, m+n+p=7~16] can be used.

[0027] Alternatively, polyamines can be used in the same manner to react with isocyanate-terminated silanes via urea linkages. Polyurea silanes can be made from a wide range of molecular, oligomeric or polymeric polyamines having at least two primary or secondary amine groups per molecule, preferably three or four amines. Polyamines with molecular weights of 50 to 10,000 g / mol, preferably 100 to 1000 g / mol, may be used. For example, diethylenetriamine or JEFFAMINE® amines, such as JEFFAMINE® T-403 polyetheramine, commercially available from Huntsman Petrochemical Corporation, can be used satisfactorily.

[0028] As used herein, the term "polyamine" refers to an aliphatic or aromatic compound containing two or more primary or secondary amine functional groups. The polyamine compound may have any suitable backbone structure, including saturated or unsaturated, linear, branched or cyclic. Representative polyamines include diamines having the following structure: [ka] [In the formula, x=2 to 70, preferably x=2 to 7] Examples of the polyether amines include those mentioned above.

[0029] Alternatively, the polyetheramine is a triamine having the structure: [ka] [In the formula, n=0 to 5, and x+y+z=3 to 100] Preferably, n=1 and x+y+z=5 to 6.

[0030] B. Inorganic metal alkoxides The inorganic metal alkoxide component of the coating material includes at least one metal alkoxide, including those based on Si, Ti, Zr, B, Al, Ge, V, Pb, Sn, Zn, etc. Silicon alkoxides are preferred. The silicon alkoxides may include monofunctional organic moieties such as epoxide, alkyl, phenyl, vinyl, mercapto, methacrylate, etc., or may be bis-silane terminated, such as bistrimethoxysilylethane.

[0031] Preferred metal alkoxides contain at least one silane group, Si(R1), per molecule. x (R2) 4-x The metal alkoxide comprises at least one hydrolyzable compound having the formula: [wherein R1 is an alkyl group (e.g., C1-C8), a polymerizable group (e.g., epoxide, vinyl, acrylic) or an alkyl group terminated with another organic moiety (hydroxyl, isocyanate, amino, thiol, etc.), R2 is a hydrolyzable group (e.g., alkoxy) or halogen, preferably methoxy, ethoxy or chloro, and x is 0, 1, 2, or 3. Preferably, the metal alkoxide is tetraethoxysilane or tetramethoxysilane.

[0032] C. Metal oxide particles Optionally, metal oxide particles may be used in the coating formulation to impart desired properties such as abrasion resistance, electrical properties, or optical properties. Such particles include silica (SiO 2 ), Alumina (Al 2 O 3 ), titania (TiO 2 ) and zirconia (ZrO 2 ) wherein the element M is selected from the group consisting of Si, Ti, Zr, B, Al, Ge, V, Pb, Sn and Zn; x O y The silica (SiO 2) is preferred. For light transmission, the particles are preferably less than about 100 nm, for example, from about 1 nm to about 100 nm. A preferred particle size is granular nanoparticles with a diameter of 1 to 10 nm. If particles are present, the coating formulation may contain up to about 50% by weight, preferably about 25% to about 35% by weight, of the particles based on the total weight of the coating formulation.

[0033] D. Coloring agent If desired, colored pigments or dyes may be used in the sol-gel formulation to impart a particular color, and there may be a method of incorporating color into this disclosure. The present invention relates to coatings having a thickness of 1-25 μm, which contain 1) 0-5% by weight of colored pigments, and 2) 0-1% of colored dyes, and are composed primarily of coating solids content with or without polymers.

[0034] Examples of colored pigments include phthalocyanine-derived metal complexes, indanthrones, perylenequinacridones, diketo-pyrrolo 3,4-c pyrrole, dioxazines, diketo-pyrrolo 3,4-c pyrrole, 3-amino-1H-isoindol-1-one-oximato-metal complexes, such as Pigment Blue 15:1, Pigment Blue 15:2, Pigment Blue 15:3, Pigment Blue 15:4, Pigment Blue 15:6, Pigment Blue 16, Pigment Blue 60, Pigment Blue 64, Pigment Green 7, Pigment Green 36, and Pigment Green 37. , Pigment Red 122, Pigment Red 123, Pigment Red 149, Pigment Red 178, Pigment Red 179, Pigment Red 190, Pigment Red 202, Pigment Red 224, Pigment Red 254, Pigment Red 255, Pigment Red 257, Pigment Red 270, Pigment Red 272, Pigment Violet 19, Pigment Violet 23, Pigment Violet 29 or Pigment Violet 37, diketo-pyrrolo 3,4-c-pyrrole, dioxazine, indanthrone or perylene pigments. These organic pigments are preferably of average particle diameter (D50) less than 1 μm or are easily dispersed by high speed dispersion mixing to achieve a pigment average diameter (D50) less than 1 μm.

[0035] For example, with regard to organically dispersed pigments, one preferred coating formulation includes 29H,31H-phthalocyanato(2-)-N29,N30,N31,N32) copper(II), known as copper phthalocyanine blue pigment. Copper phthalocyanine blue exhibits low reactivity, excellent lightfastness, and is completely insoluble in water and most conventional organic solvents. Because the pigment is insoluble, it must be rapidly dispersed in the formulation. Insolubility provides the formulation with the important feature of minimal to no leaching into the surrounding medium, making the pigment easily bonded to the coatings of the present application. The combination of dispersibility, UV lightfastness, and minimal to no color leaching provides the coatings described herein with long-lasting, UV stable, and distinguishable coating color.

[0036] Other examples of coating formulations involve the incorporation of soluble or easily dispersible dyes, fine dispersions of pigments or dyes, or coloring with dyes in salt form. For example, a preferred formulation contains [4-[4-(diethylamino)-α-[4-(ethylamino)-1-naphthyl]benzylidene]cyclohexa-2,5-dien-1-ylidene]diethylammonium chloride, known as Victoria Pure Blue BO or CI Basic Blue 7. Other examples of preferred dyes are Keygloss Blue RF, Methyl Violet 2B, Methyl Violet 6B, Methyl Violet 10B, Pararoseaniline, Fuchsine, Phenolphthalein, Malachite Green, Brilliant Blue FCF, Victoria Blue B, Victoria Blue FGA, and Victoria Blue R. The dyes are high purity chloride salts of synthetic blue triarylmethanes and can be incorporated into either the polymer or catalyst coating solution components. The invention described in this disclosure includes alcohol-soluble, water-soluble, or salt forms of dyes. The use of chloride salt dyes allows for easy mixing and results in a consistent blue coating color at low concentrations. Soluble dyes, dye salts and pigment dispersions can be incorporated at about 0.1% to 5.0% by weight of the formulation. The dyes described can be extended to other colors by those skilled in the art.

[0037] Alternatively, formulations can be prepared without the presence of colorant additives, and these formulations, when coated onto a substrate, exhibit transmissive properties and remain optically and visually clear, even with the addition of selected corrosion inhibitor additives.

[0038] E. Corrosion inhibitors Aircraft surfaces are typically alloys having a major component such as aluminum and one or more minor components for mechanical reinforcement known as intermetallics. The intermetallics often contain copper, which behaves cathodically with the surrounding predominantly aluminum matrix acting anodically and thus can act as small galvanic corrosion spots. The cathodic intermetallic phases can accelerate the corrosion of aluminum through galvanic effects in the presence of electrolytes (i.e., salt water). The interaction of a wide variety of corrosion inhibitors with aluminum to reduce corrosion has been quantified in numerous sources. The unique combination of one or more of these inhibitors in the sol-gel chemistry of the embodiments described herein can enhance protective properties.

[0039] Several different types of corrosion inhibitors may be incorporated into the sol-gels of the present invention to enhance the protective properties of the resulting coating when applied to the desired substrate. The inhibitor types may include one or more of the following: compounds having one or more thiols, the primary examples being benzotriazole and mercaptobenzotriazole; hydrotalcite or hydrotalcite-like compounds, with or without additional organic modifications; zinc phosphate, zinc oxide, cerium phosphate, cerium nitrate, cerium oxide, cerium aluminum oxide; strontium aluminum polyphosphate; and zinc aluminum polyphosphate.

[0040] F. Composition and Properties The composition of the coating formulations described herein may vary depending on the desired final properties of corrosion resistance, flexibility, hardness, abrasion resistance, transparency, or other desired physical properties. In general, the weight ratio of polymeric silane to metal alkoxide or organofunctional metal alkoxide in the formulation may be about 1:9 to about 9:1, preferably about 3:1. The metal oxide particles in the formulation may be used at about 1 to 50 wt%, preferably about 10 to about 30 wt%, based on the total weight of the coating formulation. An optional colorant may be used at about 0.1 to 5.0 wt%, based on the total weight of the coating formulation.

[0041] The coating material may be prepared by mixing the inorganic and organic components with water and an aqueous acid catalyst in a suitable solvent such as isopropanol. The aqueous acid catalyst is added to initiate hydrolysis of the hydrolyzable silane groups. Preferred acid catalysts include mineral acids such as hydrochloric acid, sulfuric acid, and nitric acid, or organic acids such as acetic acid. Sufficient acid catalyst is added to reduce the pH of the reaction mixture to less than 5, preferably about 2 to about 4. The coating formulation is prepared by hydrolysis and condensation of the organic and inorganic silane components, resulting in an organic-inorganic network via Si-O-Si bonds.

[0042] The resulting coating formulation may be mixed in a solvent or may be solvent-free. If used, the solvent may be an alcohol (methanol, ethanol, propanol, isopropanol, butanol, etc.) or other water-miscible solvent such as acetone. The concentration of solids in the formulation depends on the thickness desired for the end use or the method of application. Typically, the formulation has about 5% to about 100% solids by weight based on the total weight of the coating formulation, with a preferred solids concentration being about 15% to about 25% by weight.

[0043] The liquid coating material may be applied to the substrate by conventional coating methods, including dipping, brushing, flow coating, spraying, etc. The coating material may be cured at a wide range of temperatures depending on the desired properties, e.g., abrasion resistance, flexibility, etc., or depending on the thermal limitations of the substrate to be coated. For example, the coating may be cured at about 25° C. to about 150° C., preferably about 75° C. The temperature of curing may be varied for compatibility with the substrate.

[0044] The thickness of the cured coating may be from about 0.5 μm to about 20 μm, preferably from about 4 μm to about 8 μm.

[0045] The coatings described herein are suitable for coating a variety of substrate materials to provide the substrate with enhanced corrosion resistance, chemical resistance, water repellency, liquid / gas barrier, abrasion resistance and water repellency capabilities. Suitable substrates include, but are not limited to, glass, metals such as aluminum and steel alloys, plastics such as polycarbonate and acrylic, hardened cement, concrete or grout, wood and painted surfaces. In addition, the sol-gel coatings may be primed and overcoated with a wide variety of topcoats suitable for multiple industries and applications, such as aerospace, automotive, marine and architectural industries, to name a few.

[0046] The invention will be further understood by reference to the following non-limiting examples thereof. EXAMPLES

[0047] Example 1 Coating materials containing the following formulations were applied onto glass substrates as coatings of approximately 4-8 μm thickness (Table 1). The coatings were cured at approximately 90° C. The coated substrates were then evaluated for visual clarity (Table 1).

[0048] Synthesis of silane-functionalized polyols: The polycaprolactone polyol is measured into cleaned and thoroughly dried glassware. In separate cleaned and thoroughly dried glassware, the precise molar ratio of isocyanate silane is measured (e.g. polycaprolactone diol requires twice the molar amount of isocyanate to caprolactone). The isocyanate glassware is covered with a nitrogen blanket and sealed with a rubber septum. The catalyst (dibutyltin dilaurate) is measured into the polycaprolactone polyol. For example, in one embodiment, 0.1 wt. % of catalyst is used relative to the combined isocyanate and polycaprolactone polyol measurements. The reaction vessel is then also covered with a nitrogen blanket and sealed with a rubber septum.

[0049] Set up the caprolactone polyol and catalyst to stir in an ice bath. Slowly add the isocyanate dropwise to the stirring caprolactone-catalyst mixture, using nitrogen flow to control the rate of addition. The addition step must be done over an ice bath; the reaction generates heat and the ice bath reduces the chance of side reactions. Once all the isocyanate has been added, the ice melts and the reaction is allowed to come to room temperature. Stir the reaction at room temperature for at least 6 hours. The isocyanate peak (approximately 2270 cm) should be approximately 100%. -1 The decrease in isocyanate (CO) can be measured by Fourier transform infrared (FTIR) spectroscopy. Once the isocyanate has reacted sufficiently, as evidenced by the disappearance of the isocyanate stretch in the spectrum, the polyurethane silane should be filled into a bottle and backfilled with nitrogen.

[0050] Standard Coating Synthesis (Example 1): First, the silanes are mixed. A molar ratio of 0.4 moles of organosilane and 0.6 moles of inorganic silane is typical. The solvent is then added to the silane mixture. The volume of the solvent should be approximately 50-80% of the total coating solution, but can be up to 90%, depending on the desired coating thickness. Typical solvents include isopropanol, ethanol, or 1-propanol.

[0051] After the silane is thoroughly dispersed in the solvent, acidified water is added. The water should be acidified to a molar concentration of 0.05-0.1 M depending on the desired rate of hydrolysis. Hydrochloric acid, acetic acid, or nitric acid can be used to lower the pH of the aqueous solution. The acidified water is added in a molar ratio sufficient to hydrolyze the alkoxy groups of the silane.

[0052] The coating solution is mixed for 1-2 hours to complete hydrolysis. The coating can be applied by flow coating, brush coating, spray coating or dip coating methods for best results. After coating, excess coating is brushed off the substrate before curing. The coating becomes tack-free in approximately 15 minutes at room temperature. Alternatively, the coating may be cured at 75-150°C for at least 30-60 minutes to increase hardness and toughness.

[0053] [Table 1]

[0054] A representative coated glass coupon having the cured coating formulation of Table 1 thereon is shown in FIG.

[0055] Example 2 Coating materials having the formulations shown in Table 2 were applied as coatings of approximately 4-8 μm thickness onto glass and metal substrates. The coating formulations were identical to those of Example 1, except for the use of a colorant. The coatings were cured at approximately 90° C. Standard Coating Synthesis (Example 2):

[0056] The silanes are mixed first. A molar ratio of 0.4 moles of organosilane and 0.6 moles of inorganic silane is typical. The solvent and pigment are then added to the silane mixture. 20-40% of the total amount of solvent is added and mixed thoroughly. The pigment is mixed at high speed into the solution to ensure good dispersion. Typical solvents include isopropanol, ethanol, or 1-propanol.

[0057] After the silane is thoroughly dispersed in the solvent, acidified water is added. The water should be acidified to a molar concentration of 0.05-0.1 M depending on the desired rate of hydrolysis. Hydrochloric acid, acetic acid, or nitric acid can be used to lower the pH of the aqueous solution. The acidified water is added in a molar ratio sufficient to hydrolyze the alkoxy groups of the silane.

[0058] The coating solution is mixed for 1-2 hours to complete hydrolysis. Once the silane has hydrolyzed, the coating is filtered through a 1 μm filter before coating. The coating can be applied by flow, brush, spray or dip coating techniques for best results. After coating, excess coating is brushed off the substrate before curing. The coating will become tack-free in approximately 15 minutes at room temperature. Alternatively, the coating may be cured at 75-150°C for at least 30-60 minutes to increase hardness and toughness.

[0059] The coated substrates were then evaluated for visual transparency as shown in FIG. 2, for surface properties as also shown in Table 3 and FIGS. 3A and 3B, for electrochemical behavior including electrochemical polarization as shown in FIG. 4, and for electrochemical impedance as shown in FIGS. 5A-5D.

[0060] [Table 2]

[0061] [Table 3]

[0062] Example 3 Coating materials containing the following formulation base were applied onto glass substrates as coatings of approximately 4-8 μm thickness. The coating formulations were identical to Example 1, except that the corrosion inhibitor was incorporated by the same mixing procedure outlined for the colorant in Example 2. The following commercially available inhibitors were used to prepare coatings at loadings of 5-15 wt % (based on the total weight of the formulation): Novinox® PAS (strontium aluminum polyphosphate), cerium nitrate hexahydrate, and Intelli-ion® AX1 (benzotriazolate in ion exchange resin). The coatings were cured at 90° C. The coated substrates were then evaluated for visual appearance, as shown in FIGS. 6A-6C.

[0063] Example 4 Coatings containing the following formulation bases were applied at thicknesses of approximately 4-8 μm. The coatings were identical to Example 1, except that the corrosion inhibitor was incorporated by the same mixing procedure outlined for the colorants in Example 2. The following commercially available inhibitors were used to prepare coatings at loadings of 1-5 wt % (based on the total weight of the coating formulation): Halox® 430, Halox® 550 WF, and Halox® SZP-391. The coatings were applied to 316 stainless steel fasteners and cured at approximately 90°C. The fasteners were then mated with aluminum alloy 7075-T6 flat panels using matching nuts and subjected to ASTM B117 salt spray testing for 14 days. Photographs of the results of representative coupons are shown in Figures 7A and 7B. Separately, the same coatings were applied to aluminum alloy 7075-T6 flat panels and scribed through the coating to the substrate below before also subjecting them to ASTM B117 salt spray testing for 14 days. A photograph of a representative coupon result is shown in Figure 8.

[0064] Example 5 Uncoated and sol-gel coated Ti-6Al-5V alloy fasteners and 316 stainless steel fasteners were installed in pre-drilled holes in painted 7075-T6 aluminum alloy panels as shown in the top photographs of Figures 9A and 9B, respectively. The sol-gel coated fasteners were cured prior to installation in the pre-drilled holes in the aluminum alloy 7075-T6 panels. After 500 hours of salt spray testing according to ASTM B117 and subsequent removal of the coating from the aluminum panels, the galvanic corrosion protection properties of the coatings can be clearly observed as shown in the bottom photograph of Figure 9B, compared to the poor galvanic corrosion in the case of the uncoated hardware shown in the bottom photograph of Figure 9A.

[0065] Similar results were obtained when the same sol-gel formulation was applied to 316 stainless steel fasteners and compared to commercially available AC-131 from 3M (see Figures 10A and 10B). AC-131 is a non-chromate conversion coating for use on aluminum, nickel, stainless steel, magnesium and titanium, referenced from U.S. Patent No. 10,508,205. As can be seen in Figures 10A and 10B, galvanic corrosion testing showed substantially less damage with the sol-gel formulated herein compared to the commercially available AC-131 product.

[0066] An analysis was completed to quantify the extent of corrosion damage of down-holes (non-surface) on aluminum panels with uncoated fasteners compared to the sol-gel coated fasteners shown in Figures 9A and 9B. It was visually evident from the surface appearance that the plates containing sol-gel coated fasteners suffered much less corrosion damage than the plates containing uncoated fasteners. After analyzing the statistical data from the cross-sectional metallography, it was found that all of the holes using uncoated fasteners had similar damage metrics, regardless of fastener type. The damaged down-holes were converted to anodic charge passed using Faraday's law for the alloy in terms of volumetric loss of aluminum. The results are presented in Figure 11. From this analysis, it was determined that the sol-gel coating formulation of the embodiment described herein reduced the corrosion damage of aluminum holes by more than 98% compared to the uncoated fastener condition. As such, the damage protection provided by the sol-gel coating formulations herein is expected to range from about 25% galvanic protection to complete, substantially 100% galvanic protection (e.g., about 75% to about 99%), depending on the environmental and test conditions.

[0067] While the invention has been described in terms of what are presently considered to be the most practical and preferred embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the invention.

Claims

1. A coating formulation for preventing galvanic corrosion, comprising: (i) an organic polymeric silane; and (ii) Inorganic metal alkoxides and a galvanic corrosion inhibiting amount of an acid catalyzed condensation reactant comprising:

2. 2. The coating formulation of claim 1, wherein the organic polymeric silane and the inorganic metal alkoxide are present in a weight ratio of organic polymeric silane to inorganic metal alkoxide of about 1:9 to about 9:

1.

3. 3. The coating formulation of claim 2, wherein the weight ratio of the organic polymeric silane to inorganic metal alkoxide is about 3:

1.

4. 2. The coating formulation of claim 1, wherein the organic polymeric silane is a silane-functionalized polyol or polyamine.

5. 2. The coating formulation of claim 1, wherein the organic polymeric silane is a functionalized polycaprolactone polyol having 2 to 4 hydroxyl groups reacted with an isocyanate-terminated silane.

6. 6. The coating formulation of claim 5, wherein the functionalized polycaprolactone polyol has a molecular weight of 50 to 10,000 g / mol.

7. The coating formulation of claim 1 , wherein the organic polymeric silane is a polyurea silane.

8. 8. The coating formulation of claim 7, wherein the polyurea silane is a reaction product of an amine having at least two primary or secondary amine groups and an isocyanate-terminated silane.

9. 9. The coating formulation of claim 8, wherein the polyurea silane is the reaction product of diethylenetriamine and an isocyanate-terminated silane.

10. The metal alkoxide has at least one group of the formula Si(R 1 ) x (R 2 ) 4-x [In the formula, R 1 is C 1 ~C 8 Alkyl group, epoxide group, vinyl group, acrylic group, R 2 10. The coating formulation of claim 9, comprising at least one hydrolyzable compound having a silane group represented by the formula: x = a hydrolyzable alkoxy group or halogen; and x is 0, 1, 2 or 3.

11. From about 1 to about 50 wt %, based on the total weight of the coating formulation, of formula M x O y 10. The coating formulation of claim 1, further comprising metal oxide particles having the formula: wherein M is selected from the group consisting of Si, Ti, Zr, B, Al, Ge, V, Pb, Sn, and Zn, and y is an integer.

12. 5. The coating formulation of claim 4, wherein the metal oxide particles are selected from the group consisting of silica, alumina, titania and zirconia.

13. The coating formulation of claim 5, wherein the metal oxide particles are substantially spherical nanoparticles having an average diameter of 1 to 10 nm.

14. 10. The coating formulation of claim 1 further comprising 0.1 to 5.0 wt. % of a colorant, based on the total weight of the coating formulation.

15. 8. The coating formulation of claim 7, wherein the colorant is an organic color pigment or an organic dye.

16. The coating formulation of claim 1 further comprising a corrosion inhibitor.

17. 10. The coating formulation of claim 9, wherein the corrosion inhibitor is selected from the group consisting of compounds having one or more thiols, modified and unmodified hydrotalcite compounds, zinc phosphate, zinc oxide, cerium phosphate, cerium nitrate, cerium oxide, cerium aluminum oxide; strontium aluminum polyphosphate and zinc aluminum polyphosphate.

18. 1. A method for preventing galvanic corrosion of a metal component, comprising: (a) applying the coating formulation of claim 1 onto a metal part in the presence of an acid catalyst; and (b) curing the coating formulation on the metal component to prevent galvanic corrosion when the metal component is subsequently contacted with a second metal component. A method comprising:

19. 13. A galvanic corrosion inhibiting assembly comprising first and second metal parts in contact with one another, at least one of the first and second metal parts comprising thereon a cured coating of the acid catalyzed coating formulation of claim 1.

20. 20. The assembly of claim 19, wherein the assembly exhibits between about 1% and about 100% reduction in galvanic corrosion as compared to an assembly of the first and second metal components not having the hardened coating thereon.

21. 1. An assembly including first and second metal components in contact with one another, at least one of the first and second metal components comprises thereon an acid catalyzed cured coating of the coating formulation of claim 1; The coated assembly further comprises a secondary coating applied over the cured coating.

22. 1. A method of providing galvanic protection to a metal assembly including first and second metal components in contact with one another, comprising the steps of: (a) applying a galvanic protective coating of the coating formulation of claim 1 onto at least one of the first and second metal components; (b) connecting the first and second metal parts in contact with one another to form an assembly thereof; (c) curing the galvanic protective coating, either before or after step (b), to form a cured galvanic protective coating; and (d) applying a secondary coating over the assembly of the first and second metal components. A method comprising:

23. 23. A coated metal assembly produced by the method of claim 22.

Citation Information

Patent Citations

  • High polymer coating applied to stainless steel lined composite tube

    CN109337574A

  • High solid zinc dust coating

    JP1978016044A

  • Silane-containing isocyanate prepolymer

    JP1986007317A

  • High strength heavy duty corrosion protection covered steel member having impact resistant fixed edge part

    JP2004002941A

  • Silane-based water-based corrosion inhibitors

    JP2014515771A